2020
DOI: 10.1016/j.ajp.2020.102092
|View full text |Cite
|
Sign up to set email alerts
|

Epidemic of COVID-19 in China and associated Psychological Problems

Abstract: The world is experiencing pandemic of the COVID-19 now, a RNA virus that spread out from Wuhan, China. Two countries, China first and later Italy, have gone to full lock down due to rapid spread of this virus. Till to date, no epidemiological data on mental health problems due to outbreak of the COVID-19 and mass isolation were not available. To meet this need, the present study was undertaken to assess the mental health status of Chinese people. An online survey was conducted on a sample of 1074 Chinese peopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

118
1,065
28
142

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,147 publications
(1,353 citation statements)
references
References 29 publications
118
1,065
28
142
Order By: Relevance
“…This finding is higher than studies conducted in Hubei Province, China (37.1%) [36], and 194 cities in China (16.5%) [34]. Furthermore, our study showed that nearly three-fourth (71.8%) of students had experienced anxiety disorders during the lockdown.…”
Section: Discussioncontrasting
confidence: 84%
“…This finding is higher than studies conducted in Hubei Province, China (37.1%) [36], and 194 cities in China (16.5%) [34]. Furthermore, our study showed that nearly three-fourth (71.8%) of students had experienced anxiety disorders during the lockdown.…”
Section: Discussioncontrasting
confidence: 84%
“…Recent studies have similarly shown that COVID-19 affects mental health outcomes such as anxiety, depression, and post-traumatic stress symptoms. [20]- [22] Anxiousness among International university students about COVID-19 may have been associated with the impact of the virus on their research [23]and future employment [24]. On the other hand, the nervousness among students can also have been brought about by the way of progressively growing distances between humans ensuing from the quarantine.…”
Section: Comparisons Of Neuropsychological Featuresmentioning
confidence: 99%
“…Quarantine restrictions signi cantly impact on community mental function, with both con nement and boredom identi ed as particularly negative aspects of this experience (42,(45)(46)(47)(48)(49)(50). Many studies (43,47,(51)(52)(53)(54)(55) found community prevalence >25% for depression, anxiety, distress and generally poor mental wellbeing during the acute pandemic phase. However, lower prevalence rates for anxiety (56) and post-traumatic stress symptoms (45) were also recorded at the height of the SARS pandemic.…”
Section: Resultsmentioning
confidence: 99%
“…A range of individual factors are also particularly associated with poorer mental function for patients, including being a young or older adult; female gender; less education, social capital and sense of control in life; employment as HCWs; using less substances, nancial stress, unemployment and experiencing stigma or discrimination (32,33,35,40,53,55,69,75,76). Identi ed mental health risk factors for community members include age, gender, trait anxiety, personal or family history of mental illness, prolonged quarantine, direct contact with coronavirus patients, and inadequate food, clothing and accommodation (40,43,48,49,52,54,77). Community members also highlighted disruptions to expectations and life aspirations as having a particularly negative impact (78).…”
Section: Bodily Risk and Protective Factorsmentioning
confidence: 99%
See 1 more Smart Citation